Prevalence and risk factors for pre-hypertension and hypertension amongst school going adolescents in a rural area: an observational study - Fadnis, Vidya P.; Poyekar, Subhash P.; Ambike, Deepali A.; Lazar, Shraddha (International Journal of Contemporary Pediatrics, 2020)
Background: Hypertension seen in childhood can progress into adulthood thereby increasing morbidity and mortality due to cardiovascular diseases in adulthood. Younger the age of onset of hypertension, the greater is the reduction of life expectancy if left untreated. With increase in incidence of elevated blood pressure and hypertension in children; it is important to measure and record blood pressure along with weight and height at least once a year as recommended by National Institute of Health (NIH) task force of USA. Aims and objectives was to determine the prevalence of pre-hypertension and hypertension and to identify the associated risk factors for them in school going adolescents. Methods: An observational/cross-sectional study conducted among adolescents studying between Std 5th to Std 9th. A total 507 students belonging to the age group of 10-17 years were examined. Anthropometric measurements were taken to calculate Body Mass Index (BMI) and Blood pressure was measured by using mercury sphygmomanometer. Gender, age and height were considered for determining hypertension. Results: Amongst the 507 children, prevalence of pre-hypertension was 15.4% and that of hypertension was 10.85%. The study also revealed statistically significant higher prevalence of hypertension in males than in females. Family history of hypertension and dietary habits, obesity were positively correlated with higher prevalence of hypertension. A higher prevalence of pre-hypertension and hypertension was seen in the present study group compared to the similar studies in the state. Conclusions: The prevalence of pre-hypertension and hypertension among adolescent school children was 15.38% and 10.8% respectively. Possible risk factors for this current trend may be the increasing sedentary life style, faulty eating habits, and increased fat/salt contents of diet. The results suggest the need for more public awareness and prevention programs for childhood obesity and hypertension.